Pavement Aristocrats - The Bergies of Capetown - Verster, François (Francois Verster, 1998)
Duration: 00:57:00 Through a series of interviews with an historian and social workers, the film traces the bergie community back to their Khoisan roots, outlines colonial dispossession, and exposes the modern-day alcohol dependency deliberately set up by the tot system used on the Cape’s wine farms. The film also gives a chanceto these dispossed people to tell their own story. It does so by zooming in on the daily life of two couples, highlighting their inimitable wit in the face of despair, their weakness, and in the end, the dignity of choice that allows them to survive.